STUDYING THE EFFECTIVENESS OF USING ELECTRONIC DIARY AND ELECTRONIC MAGAZINES IN THE SCHOOLS OF UZBEKISTAN - Farxodova Nigina Muminjon qizi (Journals Park Publishing, 2024)
This in the article Uzbekistan in their school’s electron diary and electron from journals use efficiency is studied. Electronic diary and of the magazine education to quality influence, parents and teachers between communication in improvement instead of, as well as time and resources in savings advantages analysis will be done. Also, these systems current in reaching surface coming problems, including internet infrastructure, technical services and of teacher’s qualification with depends issues seeing will be released. Summary by doing in other words, electronic diary and journal systems study process modernization in doing important tool the fact that is emphasized.
Keywords: Electronic daily, electronic magazine, Uzbekistan schools, education efficiency, digital education system, teacher-parent communication, education process, technologies in education, education quality, internet infrastructure.